Hypopotassemia in Infantile Diarrhoea Treated With Half Strength Ringer's Lactate in Dextrose 2.5% - M. Djalinson Purba; Sjabaroedin Loebis; Djaman Purba; Sahat Halim; A. H. Sutanto; Helena Siregar (Indonesian Pediatric Society, 1982)
From October 15 until December 15, 1978, 13 children with acute enteritisadmitted to the Pediatric ward, Pirngadi Hospital Medan and treated with i. v.half strength Ringer's lactate in Dextrose 2.5% had been evaluated for hypopotassemia. Criteria used were a serum potassium level of less than 4 mEq /L and the typical ECG pattern.Out of the 13 patients, 10 (79,6%) developed hypopotassemia during i. v.therapy. It is concluded that in cases of Pediatric gastroenteritis treated with half strength Ringer's lactate in Dextrose 2,.% the possibility of hypopotassemia should be seriously borne in mind.